Morbidity and mortality after general surgery in heart and lung transplant patients - Alek Zywot, MD, MPH; Amber L. Turner, MPH; Joanna Sesti, MD; Russell C. Langan, MD; Andrew Nguyen, MD; Andreas R. de Biasi, MD; Siva Raja, MD, PhD; Usman Ahmad, MD; Subroto Paul, MD, MPH (Surgery Open Science, 2020)
Background: Heart and lung transplant patients can develop conditions necessitating general surgery procedures. Their postoperative morbidity and mortality remain poorly characterized and limited to case series from select centers. Methods: The National Inpatient Sample (1998–2015) was used to identify 6433 heart and 3015 lung transplant patient admissions for general surgery procedures. For a comparator group, we identified 23,764,164 nontransplant patient admissions for the same procedures. Patient morbidity and mortality after general surgery were compared between transplant patients and nontransplant patients. Data were analyzed with frequency tables, χ2 analysis, and a mixed-effects multivariate regression. Results: Overall mortality was higher and length of stay longer in the transplant group compared to the nontransplant group. Analysis revealed that hospital size and comorbidities were predictors of mortality for patients undergoing certain general surgery procedures. Transplant status alone did not predict mortality. Conclusion: Our findings demonstrate that heart and lung transplant patients, compared to nontransplant patients, have more complications and a higher length of stay after certain general surgery procedures.